2011
DOI: 10.1002/humu.21541
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pathway mutation profiles highlights collaboration between cancer-associated superpathways

Abstract: The biological interpretation of the complexity of cancer somatic mutation profiles is a major challenge in current cancer research. It has been suggested that mutations in multiple genes that participate in different pathways are collaborative in conferring growth advantage to tumor cells. Here, we propose a powerful pathway-based approach to study the functional collaboration of gene mutations in carcinogenesis. We successfully identify many pairs of significantly comutated pathways for a large-scale somatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…They found that some of them (such as the RAS and TP53 blocks in central nervous system, pancreas, skin, and blood tumors) would collaboratively promote cancer signaling and foster tumorigenesis. Using 18 pathways enriched with mutations in lung adenocarcinoma [8], Gu et al investigated pathway cooperation in cancer cells in terms of superpathways, which are clusters of co-disrupted pathways whose significance is tested by the hypergeometric model [25]. More recently, Gu et al devised a heuristic approach to detect cooperative functional modules in the glioblastoma multiforme (GBM) altered network which is obtained by mapping mutated genes onto a protein interaction network from the Pathway Commons database, and several pairs of significantly co-altered modules were identified which are involved in the main pathways known to be perturbed in GBM [26].…”
Section: Introductionmentioning
confidence: 99%
“…They found that some of them (such as the RAS and TP53 blocks in central nervous system, pancreas, skin, and blood tumors) would collaboratively promote cancer signaling and foster tumorigenesis. Using 18 pathways enriched with mutations in lung adenocarcinoma [8], Gu et al investigated pathway cooperation in cancer cells in terms of superpathways, which are clusters of co-disrupted pathways whose significance is tested by the hypergeometric model [25]. More recently, Gu et al devised a heuristic approach to detect cooperative functional modules in the glioblastoma multiforme (GBM) altered network which is obtained by mapping mutated genes onto a protein interaction network from the Pathway Commons database, and several pairs of significantly co-altered modules were identified which are involved in the main pathways known to be perturbed in GBM [26].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Gu et al [9] analyzed the co-mutation profile of pathways in the same lung adenocarcinomas data as we used here. However, without appropriate adjustment of gene length, several pathways that are known to harbor long genes were included in their co-mutated pathway network, such as axon guidance, long-term potentiation, and long-term depression [9]. These pathways function in neuro- and brain-systems, but there is rare evidence showing their functions related to cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A 2×2 contingency table was subsequently formulated, and Fisher's exact test was performed to indicate whether the mutation profiles of the two pathways were correlated. Of note, unlike the previous studies which typically counted all pathways that were involved [9], here we only included the significantly enriched pathways identified by our weighted resampling method, as the mutation events in other pathways could be raised by chance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By identifying oncogenesignaling blocks from integrated human signaling network, Cui et al [17] found that some blocks (such as the RAS and TP53) collaboratively promote cancer signaling and tumorigenesis. Gu et al [18] uncovered pathway cooperation in cancer cells in significantly co-disrupted pathways using 18 pathways enriched with mutations in lung adenocarcinoma. Gu et al [19] further identified cooperative functional modules in the glioblastoma multiforme (GBM) altered network by mapping mutated genes onto a protein interaction network.…”
Section: Introductionmentioning
confidence: 99%